2021
DOI: 10.4103/ijo.ijo_2333_20
|View full text |Cite
|
Sign up to set email alerts
|

Validation of visual acuity applications for teleophthalmology during COVID-19

Abstract: Purpose: The objective of this study was to identify and validate smartphone-based visual acuity (VA) apps that can be used in a teleophthalmology portal. Methods: The study was conducted in three phases: A survey to investigate if the SmartOptometry App was easy to download, understand and test (phase I), an in-clinic comparison of VA measured in a random testing order with four tools namely COMPlog, Reduced Snellen near vision, Peek Acuity (Distance VA) and SmartOptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…4 A different study using an Android tablet reported the mean difference was less than 0.1 LogMAR (LoAs: ±0.3 LogMAR). 13 Our findings were consistent with those of previous studies, suggesting the feasibility and practical value of mobile devices for performing different kinds of VA tests.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…4 A different study using an Android tablet reported the mean difference was less than 0.1 LogMAR (LoAs: ±0.3 LogMAR). 13 Our findings were consistent with those of previous studies, suggesting the feasibility and practical value of mobile devices for performing different kinds of VA tests.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the highest brightness of the smartphone screen was greater than that of the VA light box (425 cd/m 2 vs. 250 cd/m 2 ), and it was easier to distinguish optotypes. Some studies have shown a slight underestimation of NVA with ASC 4,13,19 or no significant difference 21 . In addition, the discrepancy in the initial size of the optotypes and settings of the testing endpoints may also be a contributing factor to the difference in results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations